Detection of Burkholderia pseudomallei in rice fields with PCR-based technique - Kao, C M; Chen, S C; Chen, Y S; Lin, H M; Chen, Y L (Folia microbiologica, 2003)
Burkholderia pseudomallei Ara- in rice fields was detected using PCR-based techniques with 16S RNA and flagella gene primer sets. The sensitivity of these PCRs was at least 1 CFU/mL of B. pseudomallei Ara- preincubated into Ashdown's medium for 6 h. B. pseudomallei Ara- DNA from watery soil were more detectable than from dry soil. The distribution of this DNA was mainly found at a depth of 300-600 mm under crop-covered fields, but not detected in the location of soil close to the land surface. The results suggest that PCR based on 16S RNA and flagella gene primer sets can be applied to investigate the presence of B. pseudomallei Ara- in contaminated soil of rice fields.
Keywords: Sensitivity and Specificity; půdní mikrobiologie; flagelin; DNA, Ribosomal; Polymerase Chain Reaction; DNA bakterií; polymerázová řetězová reakce; DNA, Bacterial; Taiwan; RNA, Ribosomal, 16S; rýže (rod); senzitivita a specificita; Soil Microbiology; Flagellin; RNA ribozomální 16S; Burkholderia pseudomallei; Oryza; ribozomální DNA